A Refined Dynamic Model of Harmonic Drive and Its Dynamic Response Analysis - Xian Zhang; Tao Tao; Gedong Jiang; Xuesong Mei; Chuang Zou (Shock and Vibration)
To highlight the key factors which influence the dynamic performance of the harmonic drive, a refined harmonic drive model considering nonlinear stiffness, kinematic error, and friction of the critical components is established. A dedicated experimental apparatus based on double motor twisting is constructed to measure the characteristics of harmonic drive, and the attribute parameters of the proposed model are identified. A series of experiments on the dynamic transmission error at different driving velocities are carried out to verify the proposed model. Based on the proposed model, the influence of different component stiffness on the velocity step response of the harmonic drive is analyzed. The results show that the influence of the component stiffness on the system dynamic response is more significant at high driving velocity, the increase of the stiffness of each component will decrease the dynamic transmission accuracy of harmonic drive, and the bearing radial stiffness is the most sensitive parameter to system’s dynamic response among all the stiffness factors.